CORRELATION OF CELLULAR AUTOLYTIC CHANGES IN BONE MARROW WITH POST-MORTEM INTERVAL - Gururaj, Biradar; Shankar M, Bakkannavar; Kumar, G Pradeep; Shaila, Bhat; Vinod C, Nayak (International Journal of Clinical and Biomedical Research, 2015)
Estimation of post mortem interval is of great importance in both civil and criminal disputes. Determining time since death is extremely difficult and accuracy can never be met. Most of the methods currently employed are temperature based algorithms, rigor mortis, livor mortis, thanato-chemistry etc. But the uncertainties attaching to traditional means of establishing the time since death have directed attention to the chemical changes in the body fluids like cerebrospinal fluid and vitreous humour along with various cellular changes in the body tissues. The study of the viability and morphological changes seen in the cells of various body tissues could provide useful information regarding post-mortem interval. In our study the cellular and cytoplasmic changes observed were time related up to 16 hours. KEYWORDS: Post mortem interval; Cellular changes; Cytoplasmic changes.